Sistem Pengelolaan Zakat Untuk Meningkatkan Usaha Produktif Masyarakat Di Kantor Badan Amil Zakat Nasional (BAZNAZ) Di Kabupaten Labuhanbatu - Ahmad Perdana Indra, Khofifah Shofy Aulia, (CV. PUSDIKRA MITRA JAYA, 2022)
In implication, the internship that the author has done for 1 month at the BAZNAS (National Zakat Amil Agency) Kab. Labuhanbatu, North Sumatra Province, has stimulated the author to be able to adapt to the environment and culture of the BAZNAS (National Zakat Agency) Kab. Labuhanbatu, both stimulated the author to work in the field of distribution in an applicative manner, as well as being able to know and analyze management, and what strategies should be carried out in each field so that it can be achieved effectively and efficiently, the management is quite good as evidenced by the work that is structured and well specialized in their respective fields of work. From this Field Work Practice opportunity, it has opened up opportunities for writers both in terms of experience, guidance, direction, and knowledge provided by the Chairman, Deputy Chair I, Deputy Chair III, Secretary, and staff so that they can improve soft skills and hard skills of the author. In correlation, the purpose of the internship has been carried out optimally for the author himself.